Le « traduire » comme paradigme de la pratique du design - Annie Gentes; Avner Perez (Appareil)
This article addresses the question of translation based on research in design and ethno-psychiatry. By comparing methodologies, we see that they implement confrontations between heterogeneous, human and non-human elements, in order to create new propositions, representations, and meanings. This dynamic process of mixing heterogeneous elements produces solutions that are not pre-determined by the universes of the participants in the design or psychanalytical processes. In both cases, the solutions rely on a “dispositive” with specific properties and effects on the designers and psychoanalysts. We want to better understand this dispositive basing our analysis on the observation of an emblematic example of design practice : the personas and on the experience of the “Clinic of the multiplicity”. Translating is defined as the implementation of a situation of mediation that seeks to undo the conjunctions, that is to say, to dissociate the strongly linked elements in situations, speeches, objects. The participants in design situations and in the Clinic of the multiplicity do not simply welcome otherness ; they are busy both altering the situation called for within the dispositive / apparatus and allowing themselves to be altered by it in a constant to-and-fro between empirical and conceptual approaches. The translating dispositive makes it possible to accommodate a powerful increase of heterogeneous elements that can be recomposed thanks to an “organizer” that comes from the interactions and provides original solutions. In this text, we consider that “translating” describes an operation that goes beyond the otherness of a foreign text which is already given. Here, “translating” means actualizing what has the potential to exist through the original combination of heterogeneous materials. As a product of these successive alterations, translating is thus inseparable from a creative process.